(untitled) (Collection of scientific works «Modern structures of metal and wood», 2022)
Mitigation of the effects of the explosion is in the spotlight due to the unstable geopolitical situation. Existing wooden structures are not designed to withstand an explosive load, and in areas of a possible attack, their sensitive elements require anti-explosive modernization. The search for rational constructive solutions for connections that can plastically deform and dissipate the energy of an explosion, while preserving the supporting frame from destruction, is an urgent problem. The number of studies on the characteristics of connections of wooden structures under explosive loading is very limited and requires a holistic and systematic approach. Dynamic tests of connections of wooden structures using the Shock Tube installation, which is capable of creating high strain rates similar to those observed during explosions in the far zone, are presented. A load transfer device (LTD) with two third-span load transfer beams was used to convert the reflected shock tube pressure into two concentrated forces applied directly to the specimens. While the structural member is subjected to a uniformly distributed load in a real explosion, the use of LTD generates similar strain rates and general dynamic responses in the timber member and connections. The LTD consists of rigid steel panels covering the entire opening of the end frame. Thanks to the slotted hinges, the LTD can move up to 200 mm, which allows the transfer of pressure without changing the rigidity of the tested specimens. A technique for the development of energy-absorbing connections (EAC) in assemblies of glued laminated timber and cross-laminated timber (CLT) for protection against the impact of a blast wave is considered. Explosive overloads were modeled with the introduction of the Shock Tube installation. Experimental test results have shown that, when properly designed, EACs allow assemblies to withstand more blast energy than conventional glulam and CLT connections. The behavior of an EAC wood bar element under explosive loading can be divided into three stages. The initial loading stage is the region where both the EAC and the wood element behave resiliently by the time the EAC yields. The second stage is characterized by a yield plateau where EAC exhibits almost perfect ductility and the load acting on the wood element is constant. The last stage consists of a compaction stage accompanied by an increase in stiffness and strength, which exceeds the strength of the wooden element. Awareness of the need to protect wooden structures from significant dynamic effects (explosion, tornado) is an insufficiently solved problem. The analysis of literary sources made it possible to identify the advantages and disadvantages of different types of connections of wooden rod structures under the action of significant dynamic loads. Their advantages and disadvantages are determined, as well as the ways for their further improvement and application.